Economic geographies of the illegal: the multiscalar production of cybercrime - Hall, Timothy (Trends in organized crime, 2021)
Economic geographers have traditionally been reluctant to extend their analysis to illicit and illegal markets despite their being significant in their global economic extent and displaying highly uneven geographies. By contrast, the geographies of licit, legal industries have produced multiple traditions of empirically rich, theoretically diverse accounts. Our understandings of the spatialities of illicit and illegal ‘industries’ derive from a different set of intellectual traditions for whom space is a less explicit, central concern. This paper aims to advance our understanding of the geographies of illegal economic activities by exploring the spatialities of one illegal industry, cybercrime (online for-profit fraud), through the lens of economic geography. It considers the spaces within which cybercrime is embedded, exploring it as the product of factors operating at multiple scales. It reviews cybercrime scholarship focused, variously, at the local, national and transnational scales and examines factors salient to the production of cybercrime through case studies at these scales. It examines national level drivers of cybercrime, local cybercrime agglomerations in Europe and transnational asymmetries, connections and opacities and the production of cybercrime. In each case, it reflects upon the potentials for the development of more spatially informed readings of cybercrime specifically, and illegal economic activities more generally, and considers how this might be mobilised to inform anti-cybercrime policy. The paper speaks to both theme I of this special edition ‘the interactions, the norms, the rituals, the behaviours of OCGs in physical spaces’ and theme III ‘the interactions between OCGs and institutions such as the political and economic field’.